No overall impact on body mass index for age change after dolutegravir initiation in a French paediatric cohort. Issue 9 (20th March 2022) - Frange, Pierre; Avettand‐Fenoel, Veronique; Veber, Florence; Blanche, Stephane
Abstract: Objectives: Increased weight gain with dolutegravir use is increasingly scrutinized in adults, but published data in paediatrics are limited and conflicting. This study aimed to provide long‐term data about changes in body mass index (BMI) in French children (aged 3–9 years) and adolescents (aged 10–17 years) receiving dolutegravir. Patients and methods: This retrospective monocentric study included 97 subjects who received a dolutegravir‐based regimen for ≥12 months in 2014–2021. We evaluated the mean change in age‐ and sex‐matched standardized BMI z score (BMIz) per year of dolutegravir exposure and compared the dynamics of BMIz change during the 12 months pre‐ vs. post‐dolutegravir use when these data were available. Results: At the time of dolutegravir initiation, most of the subjects were antiretroviral therapy (ART) experienced (89.7%), displayed virological suppression (73.2%), and had normal weight for their age (78.4%). Median follow‐up was 30 months (interquartile range [IQR] 19–45). The mean rate of change in BMIz was +0.03 z score/year of dolutegravir exposure (95% confidence interval [CI] −0.08–0.13) in the entire cohort. It was lower in children than in adolescents (−0.08 [95% CI −0.23–0.08] vs. +0.16 [95% CI 0.06–0.26], respectively; p = 0.04) and in individuals with baseline BMI ≥50 th percentile than in those with lower BMI (−0.06 [95% CI −0.14–0.01] vs. +0.08 [95% CI −0.07–0.23], respectively; p = 0.001). Trajectories of BMIz change 12 months pre‐ vs. post‐dolutegravir were similar, except in subjects with baseline BMI ≥50 th percentile, whose rate of BMIz change was lower post‐dolutegravir (difference: −0.23 [95% CI −0.46–0.00]; p = 0.04). Conclusion: We found no evidence of change in BMIz in French children initiating dolutegravir. These reassuring findings maintain the primary position of dolutegravir among paediatric therapeutic options.